2000
DOI: 10.1111/j.1346-8138.2000.tb02264.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Dermatomyositis Associated with Mechanic's Hand

Abstract: A 67-year-old man was referred to the Department of Internal Medicine at Tokyo Medical University with interstitial pneumonia in July 1999. He presented with keratotic plaques on both palsm and on the ventral and lateral sides of his fingers. Erythematous keratosis was observed on the dosal aspect of his fingers and metatarsophalangeal (MP) joints. Edematous erythema was seen on the patient's chest, back, and the extensor surfaces of his arms. Electromyography revealed a myogenic pattern and an increased level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
3
6
0
2
Order By: Relevance
“… 4 studied mechanic’s hands in seven patients with antisynthetase syndrome indicating this skin sign for respiratory and systemic involvement. Being compatible with these observations, most cases of dermatomyositis with mechanic’s hands have been reported with IP but not with internal malignancy, while some sporadic dermatomyositis patients with mechanic’s hands were associated with malignancy 5 . In this study, we retrospectively compared the clinical characteristics in dermatomyositis of nine patients with mechanic’s hands and 30 patients without, including the presence of IP and internal malignancy, in order to reevaluate the clinical significance of mechanic’s hands as the skin sign.…”
Section: Characteristics Of Patients With Dermatomyositis Associated supporting
confidence: 77%
“… 4 studied mechanic’s hands in seven patients with antisynthetase syndrome indicating this skin sign for respiratory and systemic involvement. Being compatible with these observations, most cases of dermatomyositis with mechanic’s hands have been reported with IP but not with internal malignancy, while some sporadic dermatomyositis patients with mechanic’s hands were associated with malignancy 5 . In this study, we retrospectively compared the clinical characteristics in dermatomyositis of nine patients with mechanic’s hands and 30 patients without, including the presence of IP and internal malignancy, in order to reevaluate the clinical significance of mechanic’s hands as the skin sign.…”
Section: Characteristics Of Patients With Dermatomyositis Associated supporting
confidence: 77%
“…Previous studies indicated that various subtle skin impairments may provide clinicians and patients with important diagnostic and prognostic information 7,14,22,23,24 . However, Gottron papules or Gottron sign do not include cutaneous ulcerations.…”
Section: Discussionmentioning
confidence: 99%
“…9,15,17 As "mãos de mecânico" são caracterizadas por descamação, fissuras, ceratose e hiperpigmentação simétricas e não pruriginosas nas palmas. 15,34 Outros achados incluem edema facial, ictiose adquirida, vasculite, paniculite, perfuração de septo nasal, eritrodermia, líquen plano, doença de Degos, formação de vésico-bolhas, 5 erupção pustulosa de cotovelos e joelhos, telangiectasias gengivais, 3 eritema centrífugo flagelado (lesões raras, com eritema linear semelhante a listras de zebra), 35 dermatite herpetiforme, penfigóide bolhoso 13 e urticária. 25 Quadro raro é a variante "Wong" da DM, que apresenta hiperceratose folicular simulando pitiríase rubra pilar, com destruição folicular e miosite de mús-culos eretores do pêlo ao exame anatomopatológi-co. 13,36 Também são incomuns malacoplaquia, mucinose, 5,37 lipodistrofia, esclerodermia cutânea localizada38 e o envolvimento vulvar ou escrotal.…”
Section: Manifestações Clínicasunclassified